2004
DOI: 10.1002/hep.20158
|View full text |Cite
|
Sign up to set email alerts
|

Electric foot shock stress-induced exacerbation of α-galactosylceramide-triggered apoptosis in mouse liver

Abstract: Recently, liver natural killer T (NKT) cells, which are specifically stimulated by ␣-galactosylceramide (␣-GalCer), were found to play a critical role in intrahepatic immunity to several infections and certain hepatic disorders. However, the role of psychophysical stress on NKT cell-dependent liver injury induced by ␣-GalCer still remains to be elucidated. In this study, we employed inescapable electric foot shock as the mode of psychophysical stress and evaluated its effect on ␣-GalCer-induced hepatitis. Pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 46 publications
0
26
0
1
Order By: Relevance
“…As CD8 ϩ T cells are known to be influenced by NKT cell activation (32,33), this trend could be attributed to the downstream effects of NKT cells. NKT cell activation reportedly plays a critical role in the intrahepatic immunity to several infections and liver injury (9,34). We found ALT levels to be significantly increased after apoE treatment, which suggests that NKT cell activation contributes to sepsis-induced mortality.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…As CD8 ϩ T cells are known to be influenced by NKT cell activation (32,33), this trend could be attributed to the downstream effects of NKT cells. NKT cell activation reportedly plays a critical role in the intrahepatic immunity to several infections and liver injury (9,34). We found ALT levels to be significantly increased after apoE treatment, which suggests that NKT cell activation contributes to sepsis-induced mortality.…”
Section: Discussionmentioning
confidence: 51%
“…Studies have also shown that apoE can bind LPS, attenuate the host inflammatory response, and, thus, protect against LPS-induced mortality (8). Distinctively, apoE has also recently been implicated in the activation of NKT cells by acting as a molecular chaperone for bacterial Ags, delivering them to APCs via LDLR to activate NKT cells by CD1d, a nonclassical class-I-like Ag-presenting molecule (9). NKT cells are characterized by the NK marker (NK1.1) and a semi-invariant TCR expressing the V␣14/J␣281 gene segments.…”
mentioning
confidence: 99%
“…In brief, the liver was collected immediately after the fi nal SDR and was passed through a stainless-steel mesh, and the resulting dissociated cells were suspended in PBS, washed, resuspended in an isotonic 30% Percoll solution (Amersham, Wikströms, Sweden) containing heparin (100 U/ml, Shimizu Pharmaceutical, Shizuoka, Japan), and then centrifuged at 500 g for 15 min at room temperature. The cell pellet was resuspended in 0.83% NH 4 Cl solution for 10 min and then washed once in PBS supplemented with 2% FCS and 0.1% sodium azide (staining buffer). The number of MNCs was counted in a Bürker hemocytometer.…”
Section: Preparation Of Liver Mononuclear Cellsmentioning
confidence: 99%
“…Hepatic mononuclear cells (MNCs) were prepared as previously described [4] . In brief, the liver was collected immediately after the fi nal SDR and was passed through a stainless-steel mesh, and the resulting dissociated cells were suspended in PBS, washed, resuspended in an isotonic 30% Percoll solution (Amersham, Wikströms, Sweden) containing heparin (100 U/ml, Shimizu Pharmaceutical, Shizuoka, Japan), and then centrifuged at 500 g for 15 min at room temperature.…”
Section: Preparation Of Liver Mononuclear Cellsmentioning
confidence: 99%
See 1 more Smart Citation